Fathers - An Untapped Resource for Increasing Physical Activity among African American Girls - Tara B. Blackshear (Montenegrin Sports Academy, 2019)
African American girls' physical activity signifi cantly declines during adolescence. Single mothers are raising many African American girls. Research on the benefi ts of fathers' involvement on physical activity is minimal, especially regarding girls. Th e current study examines the impact that fathers' involvement and family structure have on physical activity behaviours among African American adolescent girls (n=40). Data were collected via a demographic questionnaire, a father involvement scale, and a leisure time exercise instrument. Data were analysed via descriptive statistics, analysis of variance, and multiple regression. African American girls' physical activity habits are positively associated with involved fathers. Girls reporting high father involvement had higher rates of physical activity than girls reporting low father involvement did. Girls from two-parent families had higher physical activity rates than girls in single-parent households, but these fi ndings were non-signifi cant. Fathers being actively engaged in physical activities was a signifi cant predictor of physical activity among the study population. Fathers demonstrating nurturing and participatory behaviours, irrespective of residential or biological status, may be instrumental in promoting physical activity among African American adolescent girls. Physical activity programming targeting African American girls should include fathers and other male fi gures, as they may be instrumental in keeping African American girls physically active.